A Complication of the Use of Fiber-Reinforced Ribbon-Composite Provisional Fixed Partial Denture in an Adolescent Patient - Tuncer, Duygu; Arhun, Neslihan; Halacoglu, Derya Merve; Oglakci, Burcu (The Journal of Dentists, 2015)
Treatment of adolescent patients with a missing incisor may be compromising because implants cannot be placed until craniofacial growth is complete. Fiber reinforced ribbon-composite fixed provisional partial dentures can be used for the replacement of the missing teeth. Since the craniofacial growth continues transverse, sagittal and vertical directions, regular control appointments must be managed to check the alveolar ridge/gingival level in the pontic area. This case report describes a clinical complication fiber reinforced ribbon-composite fixed provisional partial denture of an adolescent patient with a trauma originated missing incisor. A 14 years old male patient who had attended to Baskent University in 2010, had a traumatic dental injury in #21 tooth which was extracted. The missing tooth was replaced with a fiber reinforced ribbon-composite fixed provisional partial denture with patient’s tooth as pontic until the definitive implant supported single-tooth prosthetic rehabilitation and the family was asked to visit regularly every six months. The patient didn’t attend to the control appointments until the provisional denture’s failure and the harmony between pontic tooth and the alveolar ridge/gingiva was severely compromised after 4 years. If the goals of treatment planning favors fiber reinforced ribbon-composite fixed provisional partial denture use before skeletal maturation, attention must be given to prosthesis design. Regular control appointments of alveolar ridge and pontic design must be managed and pontic tooth must be re-shaped to accommodate physiological soft and hard tissues in accordance with the skeletal growth to ensure esthetic future single implant supported prosthetic rehabilitation without any need for further augmentation surgeries.